2004
DOI: 10.1152/ajpheart.00959.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on renal blood flow velocity during static exercise

Abstract: During exercise, activation of the sympathetic nervous system causes reflex renal vasoconstriction. The effects of aging on this reflex are poorly understood. This study evaluated the effects of age on renal vasoconstrictor responses to handgrip. Seven older (65 +/- 9 yr) and nine younger (25 +/- 2 yr) subjects were studied. Beat-by-beat analyses of changes in renal blood flow velocity (RBV; duplex ultrasound) were performed during two handgrip paradigms. Arterial blood pressure (BP) and heart rate were also m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…With regard to aging, there is growing evidence that renal vasoconstriction in response to isometric handgrip (i.e., sympathoexcitatory stimulus) is enhanced in older adults (34,42). To our knowledge, we are the first to document renal responses to the CPT in older humans.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…With regard to aging, there is growing evidence that renal vasoconstriction in response to isometric handgrip (i.e., sympathoexcitatory stimulus) is enhanced in older adults (34,42). To our knowledge, we are the first to document renal responses to the CPT in older humans.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, a better understanding of the renal circulation in older adults may have clinical relevance. However, there is currently little experimental data (42,61) regarding the effect of healthy aging on renal vasoconstriction during sympathoexcitatory stress.…”
mentioning
confidence: 99%
“…All healthy volunteers were nonsmoking, normotensive, and on no medication. Of the 11 healthy volunteers, 5 individuals were also studied in a prior report (12).…”
Section: Study Populationmentioning
confidence: 99%
“…All healthy volunteers were nonsmoking, normotensive, and on no medication. Of the 11 healthy volunteers, 5 individuals were also studied in a prior report (12).Seven RTX patients with preserved native kidneys were recruited from the renal transplantation clinic at the Hershey Medical Center. Transplant surgeries were performed 7-14 mo before the study.…”
mentioning
confidence: 99%
“…For the renal artery (RA) flow during exercise, Momen et al (12)(13)(14) observed a transient response during short bouts of handgrip exercise using ultrasound Doppler. They found that renal vasoconstriction is evoked by mechanoreflex-mediated sympathetic vasoconstriction during handgrip exercise.…”
mentioning
confidence: 99%